ACCOUNTING & FINANCE FOR BUSINESS DECISIONS - Kwan, Alvin Tzen Yet; Yap, Caroline Yu Li; Choo, Sook Yin; Wong, Evelyn Mei Ling; Foo, Yin Fah; Ho, Wai Kee; Jaspal Singh; Ng, Shir Li; Nor Irdawati Mahyuddin; Pang, Peter Looi Fai; Tan, Seng Lee; Vivi Norazlina Mohd. Sidik; et al. (SJ Learning, 2025)
Step into the world of business decision-making with Accounting and Finance for Business Decisions, written by a team of experienced academics with extensive industry experience. This introductory-level book is targeted at both undergraduate as well as postgraduate students of accounting, finance, and business. This book leverages the authors' collective knowledge and experience to provide a comprehensive guide on how to use financial information to make informed and effective business decisions. This book provides the reader with a strong foundation in accounting by unravelling the complexities of the Income Statement, Statement of Financial Position, and Statement of Cash Flows. By applying the conceptual framework of accounting and essential accounting conventions, readers will be able to understand and interpret these financial statements